Semi-rigid steel frames subjected to mainshock-aftershock earthquake sequences - Admuthe, Sushant Ajay, author; Mahmoud, Hussam, advisor; Atadero, Rebecca, committee member; Shuler, Scott, committee member (Colorado State University. Libraries, 2018)
In a typical seismic event, large number of aftershocks are generally triggered due to the complex interaction within and between tectonic plates. Despite the fact that aftershocks are typically smaller in magnitude than mainshocks, their ground-motion intensity, measured by peak ground acceleration, is not always smaller. As a result, vulnerability of structures to extensive damage and complete collapse as a result of the aftershocks increases. In spite of their in evaluating the true risk of system failure and collapse, the inclusion of aftershocks in code provisions and guidelines for seismic risk assessment and performance-based engineering is lacking. In this study, three semi-rigid frames, with connection capacity of 50%, 60% and 70% of the plastic moment of the beam, were designed and their performance under mainshock-aftershock sequences assessed. The objective of this study, pertaining to the seismic performance of the frames, was twofold. First was to develop fragility functions for the frames under sequential mainshock-aftershock hazards as the basic ingredient for performance-based engineering. Second, was to evaluate the extent of spread of inelasticity and period elongation as a result of the sequential events. The first objective was realized through performing incremental dynamic analysis (IDA) using a new set of ground-motion records, with naturally available aftershock data. Scaling of the aftershocks for the IDA was performed while maintaining the Peak Ground Acceleration (PGA) relationship, established priori, between the respective mainshock and aftershock events. The results showed that the inclusion of the aftershocks increase the probability of reaching or exceeding a particular damage state. The increase in the probability is higher for the complete damage state and lower for the slight damage state. In other words, the probability, of the structure slightly or moderately damaged in the mainshock, to exceed the same damage state is not increased in aftershocks but in the case of extensive and complete damage, there is considerable increase in the probability of exceeding the same damage state in aftershock. In addition assessment of the spread of inelasticity and period elongation, performed using Short-Term-Fourier-Transformation, show that a relationship between the elongated period and connection capacities for different ground-motion intensities can be established.
Keywords: mainshock; semi-rigid frames; period elongation; aftershock